Subcutaneous Fat Triacylglycerols Profile from Iberian Pigs as a Tool To Differentiate between Intensive and Extensive Fattening Systems - Gallardo, Emerenciana; Narváez-Rivas, Monica; Pablos, Fernando; Jurado, J. Marcos; León-Camacho, Manuel (Journal of Agricultural and Food Chemistry, 2012)
Triacylglycerols of subcutaneous fat of Iberian pigs reared on two different feeding systems, extensive and intensive, have been determined by gas chromatography with a flame ionization detector. Analyses were performed on a column coated with a bonded stationary phase (50% phenyl?50% methylpolysiloxane) with hydrogen as the carrier gas. Lipids were extracted by melting the subcutaneous fat in a microwave oven and then filtering and dissolving in hexane. A total amount of 1995 samples from several campaigns were considered. Palmitoyl-stearyl-oleoyl glycerol and palmitoyl-dioleoyl glycerol were the most abundant triacylglycerols found in the samples. A study on the discriminating power of the triacylglycerols to differentiate samples according to the pig feeding system was performed. By using the triacylglycerols as chemical descriptors, principal component analysis, linear discriminant analysis, and soft independent modeling of class analogy were applied. Dioleoyl-linoleoyl glycerol and oleoyl-dilinoleoyl glycerol were the most discriminating variables. Variable?variable plots of these two glycerols allow separation of the samples according to their content.
doi: 10.1021/jf2045312doi: 10.1021/jf2045312The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: gas chromatography; iberian pig; pattern recognition; subcutaneous fat; triacylglycerols

Water-holding capacity and instrumental texture properties of m. Longissimus dorsi and m. Serratus ventralis from Iberian pigs as affected by the production system - Tejerina, D; García-Torres, S; Cava, R (Livestock Science, 2012)
Meat from Iberian pigs had a high quality and an important acceptance for consumers, but is affected enormously by production conditions. So, in this study, ninety Iberian pigs were randomly allotted into three batches – Montanera (free-range rearing and fed on acorns and grass), Intensive (conﬁnement rearing and fed on concentrate) and Recebo (free-range rearing fed on acorn, grass and concentrate) – in order to characterize the inﬂuence of the production system on water holding capacity (WHC), drip loss, thaw loss and cook loss and instrumental texture traits of m. Longissimus dorsi and m. Serratus ventralis. Muscles from pigs raised in Montanera had greater WHC and lower water losses after thawing than those from Intensive system. Instrumental texture analysis showed that muscles from Montanera pigs had different characteristics as determined by instrumental Texture proﬁle analysis (TPA) and with most resistance to cutting of the muscle ﬁbres Warner–Bratzler (W–B). In all the cases, however, the type of muscle showed a different behaviour on water loss and rheological properties. So, these results suggest that meat quality of Iberian pig is highly inﬂuenced by the production system and type of muscle studied.
Keywords: iberian pig; Instrumental texture; Muscle; Production system; Water-holding capacity

Acorns (Quercus rotundifolia Lam.) and grass as natural sources of antioxidants and fatty acids in the “montanera” feeding of Iberian pig: Intra- and inter-annual variations - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Vázquez, F. M.; Cava, R. (Food Chemistry, 2011)
In two consecutive years (2006/2007 and 2007/2008), fortnightly samples were taken to characterise the antioxidant composition and fatty acid proﬁle of acorns and grass on which Iberian pigs feed during the period of ‘‘montanera” (free-range rearing system of the south-western of Iberian Peninsula). The antioxidant parameters analysed were: a- and c-tocopherol, total phenolics compounds (TPC), lipophilic and hydrophilic antioxidant activities (LAA, HAA) (acorn and grass) and condensed and hydrolysable tannins (CT, HT) and protein precipitating capacity (PP) (acorns). To characterise the fatty acid proﬁles, the thirteen major fatty acids were assayed. For the acorns, it was found that there was intra-annual variability in all the antioxidants studied except a-tocopherol, and inter-annual variability in all except the protein precipitating capacity. The fatty acid proﬁle also varied depending on the sampling date and the study year, especially in the saturated fatty acids (SFA) and C18:1 n-9 content. For the grass, there was intraand inter-annual variability in all the antioxidant parameters studied, and in the proportions of the fatty acids C18:0, and C18:1. It could explain variations in the antioxidant and fatty acids composition of Iberian pig tissues from animals raised in different ‘‘montanera” seasons and even in the same ‘‘montanera” season.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorn; antioxidant; fatty acid; Grass; iberian pig; ‘‘Montanera”

Authentication of fattening diet of Iberian pigs according to their volatile compounds profile from raw subcutaneous fat. - Narváez-Rivas, M; Pablos, F; Jurado, J M; León-Camacho, M (Analytical and bioanalytical chemistry, 2011)
The composition of volatile components of subcutaneous fat from Iberian pig has been studied. Purge and trap gas chromatography-mass spectrometry has been used. The composition of the volatile fraction of subcutaneous fat has been used for authentication purposes of different types of Iberian pig fat. Three types of this product have been considered, montanera, extensive cebo and intensive cebo. With classification purposes, several pattern recognition techniques have been applied. In order to find out possible tendencies in the sample distribution as well as the discriminant power of the variables, principal component analysis was applied as visualisation technique. Linear discriminant analysis (LDA) and soft independent modelling by class analogy (SIMCA) were used to obtain suitable classification models. LDA and SIMCA allowed the differentiation of three fattening diets by using the contents in 2,2,4,6,6-pentamethyl-heptane, m-xylene, 2,4-dimethyl-heptane, 6-methyl-tridecane, 1-methoxy-2-propanol, isopropyl alcohol, o-xylene, 3-ethyl-2,2-dimethyl-oxirane, 2,6-dimethyl-undecane, 3-methyl-3-pentanol and limonene.
Keywords: Gas chromatography−mass spectrometry; iberian pig; pattern recognition; subcutaneous fat; volatile compounds

Effects of herbage ingestion upon ileal digestibility of amino acids in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R.; Nieto, R.; Aguilera, J. F. (JOURNAL OF ANIMAL PHYSIOLOGY AND ANIMAL NUTRITION, 2010)
P>We conducted two experiments with heavy Iberian pigs to determine the ileal digestibility of amino acids (AA) in acorns and freshly cut herbage, and the effects of adding fresh herbage upon the supply of ileal digestible AA when pigs were fed on holm-oak acorns. In Experiment 1, carried out in cannulated pigs of 107 kg bodyweight (BW), daily intake of acorns reached 44.9 g DM/kg0.75 BW. Arg, His and Thr showed the lowest apparent ileal digestibility (AID) values, whereas Met, the branched-chain AA and Phe had the highest coefficients. The AID of total EAA was 0.716 but only 0.222 for NEAA. Most of the digestive and absorptive processes of acorn protein occurred before the hindgut. Acorn provides (per kg DM) 2.27 g apparent ileal digestible Lys and 22.7 g apparent total digestible AA. Standardized ileal digestibility (SID) values for EAA, NEAA and total AA were 0.924 +/- 0.020, 0.784 +/- 0.041 and 0.860 +/- 0.029. In Experiment 2 fresh herbage was given to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg0.75 BW) or as a supplement to acorns (28.4 g DM/kg0.75 BW). When only freshly cut forage was offered the AID of the EAA, NEAA and total AA was close to 0.65 and supplied (per kg DM ingested) 5.61 g AID Lys and 91.7 g digestible AA. Standardized ileal values were 0.744 +/- 0.023, 0.912 +/- 0.038 and 0.831 +/- 0.030 respectively. The addition of fresh forage to the acorns led to a significant decrease in AID of AA in acorn due to digesta transfer to the hindgut: His (p < 0.01), Met (p < 0.001), Phe (p = 0.092), Thr (p < 0.05) and Val (p < 0.05), but Arg, Lys and the branched-chain AA remained unaffected. The main contribution of herbage to AA nutrition of the grazing Iberian pig relies mainly on increasing the supply of digestible AA for pig tissues.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: acorns; amino acids; digestibility; herbage; iberian pig

Dimensiones y características nutritivas de las bellotas de los Quercus de la dehesa - Rodríguez-Estévez, V; García Martínez, A; Mata Moreno, C; Perea Muñoz, J M; Gómez Castro, A G (Arch. Zootec, 2008)
Acorns production of Quercus (Q. ilex, Q. suber, etc.) is an important feeding resource in the dehesa during autumn-winter. Acorn weight, size and shape present a lot of variability between species, species, individuals and areas. Also composition is variable and is influenced by its own maturation process and external agents (humidity, parasites, etc.). Op.osite, shell and cotyledons proportions show higher homogeneity. Shell composition has a very high level of tannins and lignin, which affects its digestibility. Kernel has a very high level of glucids (80% of DM) and lipids (5-10% of DM) with a oleic acid content up.er 60%, however protein level is very low (4-6% of DM). Many wild and domestic species eat acorns; however, in the dehesa, acorns are used to feed fattening Iberian pigs because this breed is the single one capable of peeling them and rises a high commercial value
Keywords: fatty acids; iberian pig; Montanera; Quercus ilex; Quercus suber; Sus scrofa

Dimensiones y características nutritivas de las bellotas de los Quercus de la dehesa - Rodríguez-Estévez, V.; García Martínez, A.; Mata Moreno, C.; Perea Muñoz, J. M.; Gómez Castro, A. G. (Arch. Zootec, 2008)
Acorns production of Quercus (Q. ilex, Q. suber, etc.) is an important feeding resource in the dehesa during autumn-winter. Acorn weight, size and shape present a lot of variability between species, species, individuals and areas. Also composition is variable and is influenced by its own maturation process and external agents (humidity, parasites, etc.). Op.osite, shell and cotyledons proportions show higher homogeneity. Shell composition has a very high level of tannins and lignin, which affects its digestibility. Kernel has a very high level of glucids (80% of DM) and lipids (5-10% of DM) with a oleic acid content up.er 60%, however protein level is very low (4-6% of DM). Many wild and domestic species eat acorns; however, in the dehesa, acorns are used to feed fattening Iberian pigs because this breed is the single one capable of peeling them and rises a high commercial value
Keywords: fatty acids; iberian pig; Montanera; Quercus ilex; Quercus suber; Sus scrofa

Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C J; Tomás Barberán, F a; Espin, J C; López Carrasco, C; Olivares, A; Rey, a I (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
Keywords: Curculio; fat; fatty acid; iberian pig

Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C. J.; Tomás Barberán, F. a; Espin, J. C.; López Carrasco, C.; Olivares, A.; Rey, a I. (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
The following values have no corresponding Zotero field: accession-num: 22064301
Keywords: Curculio; fat; fatty acid; iberian pig

Effects of herbage ingestion on the digestion site and nitrogen balance in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R; Nieto, R; Lachica, M; Aguilera, J F (LIVESTOCK SCIENCE, 2007)
We conducted two experiments in heavy-weight Iberian pigs to determine: a) the effect of lysine or protein addition - the former as L-lysine-HCl, the latter by fresh cut herbage supplementation - on protein deposition when they were fed on holm-oak acorns; b) the digestibility of energy and nutrients in acorns and freshly cut, mixed herbage; and c) a possible change in the partition of digestion along the gastro-intestinal tract of the pigs fed on acorns with the inclusion of herbage. In Experiment 1, carried out in eight cannulated pigs, the daily intake of acorns reached 44.9 g DM/kg(0.75) BW and the addition of 0.58 g L-lysine/kg of whole acorns failed to alter N retention significantly (P > 0.05). We obtained high coefficients for the apparent total-tract digestibility of dry matter (ApDM(tt), 0.84) and organic matter (ApOM(tt), 0.86) and of gross energy (ApGE(tt), 0.84) in whole acorns. The corresponding ileal values were 0.71, 0.74 and 0.74. The N balance was on average - 1.08 g/day. In Experiment 2, fresh herbage containing principally legumes was offered to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg(0.75) BW) or as a supplement to acorns (28.4 g DM/kg(0.75) BW; in this case the herbage accounted for 22% of the daily DM intake). The apparent ileal digestibilities of OM and GE for herbage accounted for 70 to 77% of the values observed at total-tract level (0.65 and 0.64 respectively). N retention reached 4.21 g/day. Average ApDM(tt), ApOM(tt) and ApGE(tt) in the herbage/whole-acorn mixture were slightly above 0.74. The intake of freshly cut herbage as complementary feed to acorns resulted in a significant transference of digesta from the small intestine to the hind gut together with a substantial decrease in ileal digestibility of nutrients and energy (P < 0.001) and a moderate decline in digestibility at throughout the whole tract (P < 0.01-P < 0.001). On the other hand, the apparent digestibility of total N increased (P < 0.001) and 31% of the N apparently digested was retained in the body of the pigs. We also observed a substantial decrease in the precaecal digestion of the DM (P < 0.01), OM (P < 0.01) and GE (P < 0.05) in acorn kernels. We concluded that the main contribution of herbage to the overall nutrient supply to the grazing Iberian pig would rely upon the provision of amino acid N and also of available minerals, both present in low quantities in acorns. (C) 2007 Elsevier B.V All rights reserved.
Keywords: acorns; digestibility; energy value; herbage; iberian pig

Effects of herbage ingestion on the digestion site and nitrogen balance in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R.; Nieto, R.; Lachica, M.; Aguilera, J. F. (LIVESTOCK SCIENCE, 2007)
We conducted two experiments in heavy-weight Iberian pigs to determine: a) the effect of lysine or protein addition - the former as L-lysine-HCl, the latter by fresh cut herbage supplementation - on protein deposition when they were fed on holm-oak acorns; b) the digestibility of energy and nutrients in acorns and freshly cut, mixed herbage; and c) a possible change in the partition of digestion along the gastro-intestinal tract of the pigs fed on acorns with the inclusion of herbage. In Experiment 1, carried out in eight cannulated pigs, the daily intake of acorns reached 44.9 g DM/kg(0.75) BW and the addition of 0.58 g L-lysine/kg of whole acorns failed to alter N retention significantly (P > 0.05). We obtained high coefficients for the apparent total-tract digestibility of dry matter (ApDM(tt), 0.84) and organic matter (ApOM(tt), 0.86) and of gross energy (ApGE(tt), 0.84) in whole acorns. The corresponding ileal values were 0.71, 0.74 and 0.74. The N balance was on average - 1.08 g/day. In Experiment 2, fresh herbage containing principally legumes was offered to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg(0.75) BW) or as a supplement to acorns (28.4 g DM/kg(0.75) BW; in this case the herbage accounted for 22% of the daily DM intake). The apparent ileal digestibilities of OM and GE for herbage accounted for 70 to 77% of the values observed at total-tract level (0.65 and 0.64 respectively). N retention reached 4.21 g/day. Average ApDM(tt), ApOM(tt) and ApGE(tt) in the herbage/whole-acorn mixture were slightly above 0.74. The intake of freshly cut herbage as complementary feed to acorns resulted in a significant transference of digesta from the small intestine to the hind gut together with a substantial decrease in ileal digestibility of nutrients and energy (P < 0.001) and a moderate decline in digestibility at throughout the whole tract (P < 0.01-P < 0.001). On the other hand, the apparent digestibility of total N increased (P < 0.001) and 31% of the N apparently digested was retained in the body of the pigs. We also observed a substantial decrease in the precaecal digestion of the DM (P < 0.01), OM (P < 0.01) and GE (P < 0.05) in acorn kernels. We concluded that the main contribution of herbage to the overall nutrient supply to the grazing Iberian pig would rely upon the provision of amino acid N and also of available minerals, both present in low quantities in acorns. (C) 2007 Elsevier B.V All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: acorns; digestibility; energy value; herbage; iberian pig

Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V.; García, A.; Perea, J.; Mata, C.; Gómez, A. G. (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus

Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V; García, A; Perea, J; Mata, C; Gómez, A G (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus

Effect of feeding system on the growth and carcass characteristics of Iberian pigs, and the use of ultrasound to estimate yields of joints. - Daza, a; Mateos, A.; López Carrasco, C.; Rey, A.; Ovejero, I.; López-Bote, C. J. (Meat science, 2006)
Forty three-castrated male Iberian pigs of the Torbiscal line with an average initial weight of 102.27kg were used. A group of 22 pigs was fed according to the traditional way in free-range conditions with acorn and grass from November to January. Another group of 21 animals was fed 3.72kg/day of a conventional feed that contained 12.53MJME/kg, 16.21% crude protein, 4.94% fat and 6.64% of crude fiber, during the same period. Measurements of backfat thickness and Longissimus dorsi muscle area at the last rib were taken by means of a real-time ultrasound device (Kretz Technick Inc., 600 V-V2.32, Sonovet, Austria) in all pigs before slaughter. After slaughter, carcass, ham and foreleg weights and backfat and muscle area measurement from the last rib chop were recorded. The average daily gain, carcass yield, fat thickness, loin area, ham weight and proportion of hams were significantly higher (P<0.05) in the pigs fed in confinement than in those fed extensively (653.36g, 77.97%, 56.46mm, 3031mm(2), 22.26kg and 14.32% vs 501.48g, 76.94%, 51.74mm, 2673mm(2), 21.52kg and 13.79%, respectively). This paper shows the prediction equations for hams, forelegs and total hams and forelegs weights and proportions with respect to slaughter weight and live ultrasound measurements in pigs fed either extensively or in confinement. The ultrasound measurements better predicted the carcass cuts absolute amounts (R(2)=0.591-0.875) than the carcass cuts proportions (R(2)=0.23-0.40). The use of real-time ultrasound should be used with caution to predict the absolute quantities of hams and forelegs from Iberian pigs since the ultrasound measurements are only moderately accurate.
The following values have no corresponding Zotero field: accession-num: 22061368
Keywords: carcass; feeding; Growth; iberian pig; ultrasounds

Effect of feeding system on the growth and carcass characteristics of Iberian pigs, and the use of ultrasound to estimate yields of joints. - Daza, a; Mateos, A; López Carrasco, C; Rey, A; Ovejero, I; López-Bote, C J (Meat science, 2006)
Forty three-castrated male Iberian pigs of the Torbiscal line with an average initial weight of 102.27kg were used. A group of 22 pigs was fed according to the traditional way in free-range conditions with acorn and grass from November to January. Another group of 21 animals was fed 3.72kg/day of a conventional feed that contained 12.53MJME/kg, 16.21% crude protein, 4.94% fat and 6.64% of crude fiber, during the same period. Measurements of backfat thickness and Longissimus dorsi muscle area at the last rib were taken by means of a real-time ultrasound device (Kretz Technick Inc., 600 V-V2.32, Sonovet, Austria) in all pigs before slaughter. After slaughter, carcass, ham and foreleg weights and backfat and muscle area measurement from the last rib chop were recorded. The average daily gain, carcass yield, fat thickness, loin area, ham weight and proportion of hams were significantly higher (P<0.05) in the pigs fed in confinement than in those fed extensively (653.36g, 77.97%, 56.46mm, 3031mm(2), 22.26kg and 14.32% vs 501.48g, 76.94%, 51.74mm, 2673mm(2), 21.52kg and 13.79%, respectively). This paper shows the prediction equations for hams, forelegs and total hams and forelegs weights and proportions with respect to slaughter weight and live ultrasound measurements in pigs fed either extensively or in confinement. The ultrasound measurements better predicted the carcass cuts absolute amounts (R(2)=0.591-0.875) than the carcass cuts proportions (R(2)=0.23-0.40). The use of real-time ultrasound should be used with caution to predict the absolute quantities of hams and forelegs from Iberian pigs since the ultrasound measurements are only moderately accurate.
Keywords: carcass; feeding; Growth; iberian pig; ultrasounds

Prediction of the feeding background of Iberian pigs using the fatty acid profile of subcutaneous, muscle and hepatic fat. - Ruiz, J; Cava, R; Antequera, T; Martín, L; Ventanas, J; López-Bote, C J (Meat science, 1998)
Thirty Iberian pigs weighing 95 kg were randomly distributed into three groups of 10 animals each and fattened in three traditional management systems ['montanera' (MO), fed extensively on acorns, 'cebo' (CE) fed on a commercial diet and 'recebo' (RE), fed on acorns and a commercial diet]. Fatty acids from the Masseter muscle, lard and liver were analysed. In the lard, fatty acid profiles from MO and RE pigs presented minor differences; however, in the liver, RE pigs showed differences to MO pigs in most of the fatty acids studied. This suggests that the muscle and especially the liver fatty acid profile reflects the feeding regime during the last phase of feeding, while the lard reflects longer term differences.
Keywords: Fatty acid profile; Feeding regime (voyant); iberian pig

Sustained utilization of the Iberian pig breed. - López-Bote, C J (Meat science, 1998)
The Iberian pig is one of the scarce non-improved swine breeds which survives the modern techniques of pig production based on improved genotypes. This is attributed both to its perfect adaptation to the Mediterranean natural ecosystem and the high quality of its products. The production of meat products from Iberian pigs has very little in common with that of meat products obtained from selected pigs raised under intensive conditions, and it constitutes an example of the preparation of high quality meat products, comparable to the most exquisite food products in the world. The production of Iberian pig is deeply bound to the Mediterranean ecosystem. It is a rare example in the world swine production where the pig contributes so decisively to the preservation of the ecosystem. The aim of this review is to describe in detail the traditional feeding of the Iberian pigs in La Dehesa and to discuss some aspects of the use of alternatives to this production system. Some of the experience in the formulation of compounds feeds for Iberian pigs and in the processing of meat products could be useful in the feeding of other pig genotypes and in different meat processing strategies.
Keywords: Dehesa; high quality products (voyant); iberian pig; Meat Products; Montanera

Influence of finishing diet on fatty acid profiles of intramuscular lipids, triglycerides and phospholipids in muscles of the Iberian pig. - Cava, R; Ruiz, J; López-Bote, C; Martín, L; García, C; Ventanas, J; Antequera, T (Meat science, 1997)
Thirty Iberian × Duroc pigs allotted in groups of ten animals were fed in three traditional different management systems ('Montanera' (MO), fed on acorns; 'Recebo' (RE), fed on acorns and a commercial diet; and 'Cebo' (CE), fed on a commercial diet). Masseter muscle was obtained to evaluate the influence of management system on fatty acid (FA) composition of lean. The FA composition of the intramuscular total lipids, triglyceride (TG) and phospholipid (PL) fractions was evaluated. Muscle from MO pigs had greater quantities of monounsaturated fatty acids (MUFA) in the total lipids, triglyceride and phospholipid fractions than the other feedings. The percentage of saturated fatty acids (SFA) of i.m. total lipids and TGs increased (P < .05) with duration of feeding on RE and CE, from 35.13-35.10% in MO pigs to 37.47-37.84% in RE pigs and 39.98-41.11% in CE pigs. PLs from RE and CE pigs contained more C(18:2) and C(20:4) and less C(18:1) than MO pigs.
Keywords: Fatty acid profile (PG); Feeding system; iberian pig

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA - Esparrago, F.; Vázquez, F. M.; Burzaco, A.; Perez, M. C. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: acorn; Econorny; evergreen oak; feeding; iberian pig; production; Quercus

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA - Esparrago, F; Vázquez, F M; Burzaco, A; Perez, M C (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.
Keywords: acorn; Econorny; evergreen oak; feeding; iberian pig; production; Quercus